Circulating Interleukin-37 Levels in Healthy Adult Humans – Establishing a Reference Range - Santarelli, Danielle M.; Vincent, Fabien B.; Rudloff, Ina; Nold-Petry, Claudia A.; Nold, Marcel F.; Russo, Marc A. (Frontiers in Immunology, 2021)
Interleukin (IL)-37 has an important function in limiting excessive inflammation. Its expression is increased in numerous inflammatory and autoimmune conditions and correlates with disease activity, suggesting it could have potential as a disease biomarker. Despite this, a reference range has yet to be determined. Our aim was to establish the first reference range of circulating IL-37 levels in healthy adult humans. PubMed was searched for studies reporting blood IL-37 concentrations in healthy adult subjects as measured by enzyme-linked immunosorbent assay. Nineteen studies were included in the analysis. Mean IL-37 levels were weighted by sample sizes, and weighted mean lower and upper levels (±2SD of means) were calculated to provide a weighted mean and reference range. IL-37 levels were quantified in either serum or plasma from a total of 1035 (647 serum; 388 plasma) healthy subjects. The serum, plasma and combined matrix weighted means (reference ranges) were 72.9 (41.5 – 104.4) pg/mL, 83.9 (41.1 – 126.8) pg/mL, and 77.1 (41.4 – 112.8) pg/mL, respectively. There were no significant differences between serum and plasma means and upper and lower limits. Study means and upper IL-37 levels were significantly higher in Chinese population studies. From our analysis, a preliminary reference range for circulating IL-37 levels in healthy human adults has been established. In order to determine a reliable reference range for clinical application, large, prospective, multi-ethnic, healthy population studies are necessary. In addition, demographics, sample matrix, collection, processing and storage methods potentially affecting IL-37 detection levels should be thoroughly investigated.